2017
DOI: 10.1186/s13054-017-1885-9
|View full text |Cite
|
Sign up to set email alerts
|

Video laryngoscopy does not improve the intubation outcomes in emergency and critical patients – a systematic review and meta-analysis of randomized controlled trials

Abstract: BackgroundThere is significant controversy regarding the influence of video laryngoscopy on the intubation outcomes in emergency and critical patients. This systematic review and meta-analysis was designed to determine whether video laryngoscopy could improve the intubation outcomes in emergency and critical patients.MethodsWe searched the Cochrane Central Register of Controlled Trials, PubMed, Embase, and Scopus databases from database inception until 15 February 2017. Only randomized controlled trials compar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
61
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 83 publications
(62 citation statements)
references
References 64 publications
0
61
0
1
Order By: Relevance
“…Most importantly, three-quarters of the studies systematically removed predicted difficult airways, the patient population in whom one would expect to observe a performance benefit from VL. 14 Our findings suggest that VL alone provides higher first-attempt success than DL aided by other maneuvers. Commonly employed visualization aids, such as ramping (especially in obese patients), laryngeal manipulation, and bougie use, have been studied and advocated for as minimally invasive, low-risk, and inexpensive maneuvers that potentially improves DL performance.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Most importantly, three-quarters of the studies systematically removed predicted difficult airways, the patient population in whom one would expect to observe a performance benefit from VL. 14 Our findings suggest that VL alone provides higher first-attempt success than DL aided by other maneuvers. Commonly employed visualization aids, such as ramping (especially in obese patients), laryngeal manipulation, and bougie use, have been studied and advocated for as minimally invasive, low-risk, and inexpensive maneuvers that potentially improves DL performance.…”
Section: Discussionmentioning
confidence: 55%
“…An additional three studies were prehospital investigations with one comparing a non‐video device (Airtraq) to DL. Most importantly, three‐quarters of the studies systematically removed predicted difficult airways, the patient population in whom one would expect to observe a performance benefit from VL . Our findings suggest that VL alone provides higher first‐attempt success than DL aided by other maneuvers.…”
Section: Discussionmentioning
confidence: 77%
“…The devices include metallic blades [13], stylets and bougies [14], and the more recently introduced videolaryngoscope, which improves visualization of the glottis and allows a second operator to provide assistance. However, in a randomized controlled trial reported in 2017 [15] and subsequent meta-analysis [16], the routine use of a videolaryngoscope in ICU patients failed to produce higher first-pass success rates compared to the Macintosh laryngoscope and was associated with a higher risk of serious adverse events. The 2018 guidelines issued by the Difficult Airway Society [8] recommend that a videolaryngoscope should be available in all ICUs and should be considered for the first attempt when laryngoscopy is predicted to be difficult [17].…”
Section: Introductionmentioning
confidence: 99%
“…Use of a VL is an emerging technique in paediatric ED intubation and in our study was positively associated with FPS. Although a recent meta‐analysis suggested no improvement in outcomes in ED intubations with VL versus direct laryngoscopy, no children were included in that data set. The National Emergency Airway Registry investigators in North America found similar benefit in their report on 1053 paediatric ED intubations and taken together these findings are worthy of consideration and further study.…”
Section: Discussionmentioning
confidence: 99%